Design of a Vapor Recovery Unit for a Condensate Fractionation Plant to Minimize Hydrocarbon Vapor Loss (Chemical Engineering Research Bulletin, 2026)
A condensate fractionation plant recycles vapors coming from the tank batteries and from the fractionation column by a vapor recovery unit (VRU). Otherwise, these valuable hydrocarbons would be lost through flaring or venting to the atmosphere. VRU is a multi-stage compressor, with intercooler and after cooler. The VRU must be designed such that it is not over-sized or under-sized. The project examined an existing plant of 4,000 barrels/day capacity and attempted to re-design the VRU for scenario where additional 6,000 barrels/day will be added to the plant capacity. The major obstacle in this task is to correctly estimate the total volume of vapor to be handled. There is no facility for direct measurements, so the amount of vapor must be estimated from correlations and by process simulation. The volume of the by-products from the fractionation column was estimated by using software, which simulated the whole fractionation process. With the help of tank data from the site, an analytical calculation was performed to compute the amount of tank vapor. A compressor for the VRU system was designed to handle the estimated total amount of hydrocarbon vapor. The benefit of using VRU from an environmental point of view was included in this work. New technologies to minimize tank vapor loss, such as construction of floating roof tanks, were also considered. The results obtained from the calculation and simulation steps reflect actual values from the plant with minor deviation, which gave confidence in this design process. The calculations indicate that, for the proposed capacity upgradation, the required VRU compressor should have 1.62 times greater capacity and 1.63 times greater horse power in case of fixed roof tanks. With floating roof, both the additional capacity and horsepower is negligible.Chemical Engineering Research Bulletin: 24 (Issue 1): 63-69